Is there good investment advice on r/wallstreetbets? - Wildi, W (2024)
r/wallstreetbets (WSB), a subreddit where members informally share investment advice, garnered widespread interest due to its involvement in the 2021 Gamestop (GME) short squeeze. Here, we analyse whether posts on WSB can be used to predict stock returns. Looking at both the overall sentiment of the forum, and a subset of posts identified as due diligence (DD) reports, we find the forum provides little to no signal about future asset prices (with the exception of ‘meme’ stocks like GME and AMC). Given the forum’s focus on high risk positions, retail investors are at risk of substantial losses if they follow the advice or sentiment of WSB.